The Correlation between Teachers’ Competencies and Students’ Learning Outcomes in Social Science Subject - nurul, Ann (International Journal Pedagogy of Social Studies, 2018)
The low level of teachers’ competencies in carrying out learning activity will affect the low students’ learning outcomes in social science subject (IPS). This research was conducted to investigate whether there was a correlation between the competencies that the teacher possessed and the students’ learning achievements in the social science subject. The method used in this research was a correlation study by using quantitative methods. The population of this research was the 303 eighth grade students of SMP Negeri 4 Bandung. The research was employed by using a simple random sampling technique which gained 76 students as the sample. The data collection techniques in this research were questionnaire and documentation. The instrument of this research was a questionnaire with close-ended questions using Likert’s Scale. The data analysis technique in this research used a Pearson Product-Moment Correlation technique. The result of the data analysis showed that the z-test score was 0.382 which meant that Null hypothesis (Ho) was rejected and Alternative hypothesis (Ha) was accepted. Meanwhile, the significance level was 3.555, thus, Ho was rejected. It meant that the correlation between the teachers’ competencies and the students’ learning outcomes in social science subject was significant. The findings of the research showed that there was a positive correlation between the teachers’ competencies and the students’ learning outcomes in the social science subject. The correlation was categorized as low level of correlation. Therefore, the low-level of the students’ learning achievements were not only determined by the teachers’ competencies, but also determined by the other factors.